Digital Competence and Transformation Effects on Employee Performance at BPR Padma Denpasar Bali - Anak Agung Gde Alit Wiradyatmika (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The purpose of this study is to examine how employee performance at BPR Padma Denpasar Bali is impacted by digital transformation and digital competencies. Thirty employees made up the research sample, and the study employed a quantitative approach with a survey method. Questionnaires were used for data collection, and SPSS 26.0 was used for data analysis using multiple linear regression. The study's findings demonstrate that both digital transformation and employee performance are positively and significantly impacted by digital competence. With a determination coefficient value (R2) of 0.582, which indicates that 58.2% of employee performance variations can be explained by these two variables, digital competence and digital transformation taken together also significantly affect employee performance. In addition to offering management implications for training planning and digitizing operational procedures, these findings confirm the significance of enhancing employees' digital competencies and putting organizational digital transformation into practice to boost performance in BPRs. Future studies will build on this research to include additional factors that may impact workers' performance in microfinance organizations.